Fracionamento e caracterização parcial de constituintes químicos do extrato bruto de Pouteria ramiflora (Mart.) Radlk (Sapotaceae) biomonitorados pela inibição in vitro da atividade da alfa-Amilase Salivar Humana (HSA) - Moura, Vilma Lucia (2008)
The aphacarbohydrate metabolism in microorganisms, animals and plants. Humans have saliva and pancreatic alpha-amylases similar in sequence and structure to hydrolyze of alfa-(1-4) glycosidic linkages starch in the oral cavity and in the intestine. This similarities are important to initially search natural inhibitors of starch digestion that could be used as potential new drugs to control posprandial hiperglycemic throughout of in vitro approaches targeting HSA. HSA is abundant in saliva sample and has many advantages to be collected and processed allowing screening and characterization studies searching for these natural inhibitors. This review shows aspect estructural of HSA and HPA and the origin of available inhibitors and its application in terapeutics and agricultural. Moreover, discuss contradictory aspects of using phaseolamine, as food supplement to weight lost. Phaseolamine is a glycoprotein from the Phaseolus vulgaris that inhibit amylase activity such as other inhibitors.Therefore, nutraceuticals that inhibits alpha-amylase may are useful in pos-prandial hyperglycemic control with potential therapeutic application for diabetics and obeses patients. Also, the discoveries of plant amylase inhibitors can drive cloning of these inhibitors genes that can be expressed in cultivars helping in the combat of insects that cause economical lost in the agricultural.